2019
DOI: 10.29252/mlj.13.5.26
|View full text |Cite
|
Sign up to set email alerts
|

Presence of GB Virus C in Whole-Blood Derivatives: A Pilot Study

Abstract: Background and Objectives: Red blood cell (RBC) transfusion is necessary for the prevention and treatment of a variety of life-threatening injuries and diseases. However, viral contamination of these products is a great threat to recipients. Screening donors for GB virus C by nucleic acid testing is not routinely implemented worldwide. The aim of the present study was to evaluate prevalence of GBV-C RNA in whole blood/red cell components. Methods: In this cross sectional pilot study, we collected 153 units of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Kheirabad et al (2016) demonstrated a significant association between the prevalence of viruses, such as HCV and HIV in HD patients and GBV-C. Recently, the following strategies have emerged to reduce the risk of infections following blood transfusion: (1) careful donor selection, (2) regular screening of blood donors for HBV, HCV, HIV, human T-cell viruses, and cytomegalovirus (in high-incidence areas), and (3) virus removal and inactivation, particularly double inactivation of blood products and plasma derivatives, excluding complete blood or RBC components (Ghanbari et al, 2010;Kelishadi et al, 2019). The history of kidney transplantation and history of surgery also had no significant differences in prevalence of GBV-C, which is in agreement with Rinonce et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kheirabad et al (2016) demonstrated a significant association between the prevalence of viruses, such as HCV and HIV in HD patients and GBV-C. Recently, the following strategies have emerged to reduce the risk of infections following blood transfusion: (1) careful donor selection, (2) regular screening of blood donors for HBV, HCV, HIV, human T-cell viruses, and cytomegalovirus (in high-incidence areas), and (3) virus removal and inactivation, particularly double inactivation of blood products and plasma derivatives, excluding complete blood or RBC components (Ghanbari et al, 2010;Kelishadi et al, 2019). The history of kidney transplantation and history of surgery also had no significant differences in prevalence of GBV-C, which is in agreement with Rinonce et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kheirabad et al (2016) demonstrated a significant association between the prevalence of viruses, such as HCV and HIV in HD patients and GBV-C. Recently, the following strategies have emerged to reduce the risk of infections following blood transfusion: (1) careful donor selection, (2) regular screening of blood donors for HBV, HCV, HIV, human T-cell viruses, and cytomegalovirus (in high-incidence areas), and (3) virus removal and inactivation, particularly double inactivation of blood products and plasma derivatives, excluding complete blood or RBC components (Ghanbari et al, 2010;Kelishadi et al, 2019). The history of kidney transplantation and history of surgery also had no significant differences in prevalence of GBV-C, which is in agreement with Rinonce et al (2017).…”
Section: Discussionmentioning
confidence: 99%